Drug Resistance in Non-Hodgkin Lymphomas - Klener, Pavel; Klanova, Magdalena (International journal of molecular sciences, 2020)
Non-Hodgkin lymphomas (NHL) are lymphoid tumors that arise by a complex process of malignant transformation of mature lymphocytes during various stages of differentiation. The WHO classification of NHL recognizes more than 90 nosological units with peculiar pathophysiology and prognosis. Since the end of the 20th century, our increasing knowledge of the molecular biology of lymphoma subtypes led to the identification of novel druggable targets and subsequent testing and clinical approval of novel anti-lymphoma agents, which translated into significant improvement of patients' outcome. Despite immense progress, our effort to control or even eradicate malignant lymphoma clones has been frequently hampered by the development of drug resistance with ensuing unmet medical need to cope with relapsed or treatment-refractory disease. A better understanding of the molecular mechanisms that underlie inherent or acquired drug resistance might lead to the design of more effective front-line treatment algorithms based on reliable predictive markers or personalized salvage therapy, tailored to overcome resistant clones, by targeting weak spots of lymphoma cells resistant to previous line(s) of therapy. This review focuses on the history and recent advances in our understanding of molecular mechanisms of resistance to genotoxic and targeted agents used in clinical practice for the therapy of NHL.
Keywords: Drug Resistance, Neoplasm; individualizovaná medicína; záchranná terapie; Biomarkers, Tumor; lidé; Precision Medicine; nehodgkinský lymfom; Antineoplastic Agents; protinádorové látky; nádorové biomarkery; Lymphoma, Non-Hodgkin; chemorezistence; Salvage Therapy; Humans